Hyperdense Middle Cerebral Artery Sign and Ischemic Stroke with Hemorrhagic Transformation - Ariel Sosa Remón; Carmen Esther Remón Chávez; Ana Esperanza Jeréz Alvarez (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
The hyperdense middle cerebral artery sign is an imaging pattern that has an incidence from 30 to 40 % of occlusions of this artery demonstrated angiographically. It represents an early sign of poorly progressive ischemic stroke. A 56-year-old patient who began with clinical manifestations of aphasia and right hemiparesis, predominantly femoral it is presented. On admission tomography, hyperdensity of the left middle cerebral artery trajectory was observed, corresponding to an extensive ischemic stroke with hemorrhagic conversion in evolutionary scan at 72 hours. The case is presented because of how infrequent it is to make this diagnosis based on the results found in the single slice axial tomography and because there was a correlation between the images found and the subsequent clinical deterioration of the patient.